Impact of systematic HIV testing on case finding and retention in care at a primary care clinic in South Africa. Issue 12 (22nd September 2014) - Clouse, Kate; Hanrahan, Colleen F.; Bassett, Jean; Fox, Matthew P.; Sanne, Ian; Van Rie, Annelies
Abstract Objective Systematic, opt‐out HIV counselling and testing (HCT) may diagnose individuals at lower levels of immunodeficiency but may impact loss to follow‐up (LTFU) if healthier people are less motivated to engage and remain in HIV care. We explored LTFU and patient clinical outcomes under two different HIV testing strategies. Methods We compared patient characteristics and retention in care between adults newly diagnosed with HIV by either voluntary counselling and testing (VCT) plus targeted provider‐initiated counselling and testing (PITC) or systematic HCT at a primary care clinic in Johannesburg, South Africa. Results One thousand one hundred and forty‐four adults were newly diagnosed by VCT/PITC and 1124 by systematic HCT. Two‐thirds of diagnoses were in women. Median CD4 count at HIV diagnosis (251 vs. 264 cells/μl, P = 0.19) and proportion of individuals eligible for antiretroviral therapy (ART) (67.2% vs. 66.7%, P = 0.80) did not differ by HCT strategy. Within 1 year of HIV diagnosis, half were LTFU: 50.5% under VCT/PITC and 49.6% under systematic HCT (P = 0.64). The overall hazard of LTFU was not affected by testing policy (aHR 0.98, 95%CI: 0.87–1.10). Independent of HCT strategy, males, younger adults and those ineligible for ART were at higher risk of LTFU. Conclusions Implementation of systematic HCT did not increase baseline CD4 count. Overall retention in the first year after HIV diagnosis was low (37.9%), especially among those ineligible for ART, but did not differ by testing strategy. Expansion of HIV testing should coincide with effective strategies to increase retention in care, especially among those not yet eligible for ART at initial diagnosis.